Improvement Potential and Exergy Analyses of Photovoltaic Thermal with and without ∇-absorber Collector - Saprizal Hadisaputra; Muhammad Zohri; Hardani Hardani; Ahmad Fudholi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The combination of a solar thermal and photovoltaic system is called photovoltaic thermal system (PVT). The PVT system with and without -absorber has been intended to harvest both hot air and electricity. The hot air that is produced is used in the cooling process of the photovoltaic panel and then to improve the efficiency of the photovoltaic panel. The experimental investigation was conducted at the mass flow rate from 0.0069 kg/s to 0.0491 kg/s and solar radiation of 522 W/m2 and 820 W/m2 in the National University of Malaysia. The using -absorber collector increases exergy and exergy efficiency of PVT system. The improvement potential comparatively upsurges with cumulative the mass flow rate.